THE IMPACTS OF THE NEW BIDDING LAW (REMUNOM, 2024)
The theme of this work was the impacts of the new bidding law. Even though they are specific, the changes that occurred after Law 14,133/21 may have implications for the dynamics of the bidding process. The objective of the work was to indicate the main impacts of the changes promoted by Law 14,133/21 for Public Administration and society. To carry out the work, a qualitative narrative literature review was used, in books, scientific articles, theses, dissertations and laws. It was highlighted that the changes introduced by Law 14,133/2021 in the bidding scenario had a direct impact on all instances of public administration, with certain nuances that require a careful strategy. The lack of adequate planning in the face of these changes can result in significant problems, especially because there does not seem to be a concern on the part of managers to provide training for their permanent employees to deal with innovations. This is essential, since the composition of the Bidding Committee now requires the participation of permanent employees, which limits the possibility for municipal administrators to seek external experts already established in the area. The new regulations bring several significant impacts, such as greater legal certainty, an expansion of contracting options, stimulation of competitiveness and greater transparency. However, it also presents challenges for its effective implementation, including the need to train public servants, promote cultural change, improve control systems and adapt systems and processes.